DINAMIKA KASUS PENISTAAN AGAMA DI INDONESIA : (Polemik Pemaknaan Ayat-Ayat Penistaan dan UU Penodaan Agama) - Irwan Ahmad Akbar (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
Bbc.com noted that in the last 40 years in Indonesia, there were 4 major cases including Lia Eden, Arswendo, HB Jassin and Teguh Santosa. Melissa Crouch noted that at least 120 people were tried for harassing religion. However, I underline that the issue of blasphemy arises recently because it began with a case of Ahok in Kepulauan Seribu. After that case, the case of blasphemy emerged like a domino effect, leaving questions in my mind, ‘why can it be like this?'. In this study, I will try to examine how the contestation of cases of blasphemy in Indonesia is so intertwined. By using descriptive and interpretative analysis methods, I found that the polemic of the emergence of blasphemy cases in Indonesia is motivated by two things; the interpretation of certain authorities who consider that in the Koran there is a set of positive punishment for blasphemy cases. Furthermore, the Blasphemy Law in Indonesia is very biased in determining certain individuals / groups as religious opponents.